Preparation method of acid-base composite crude oil catalytic cracking catalyst
By preparing the pH composite catalysts by equivalent to the volume impregnation method and ball abrasive hybrid technology, the problem of low -carbon olefin revenue caused by the size of the existing catalyst pores has been solved, and the significant increase in high -efficiency crude oil catalytic cracking and low -carbon olefin revenue. At the same time, the environmental protection of the synthesis process is guaranteed.
Patent Information
- Application Number
- CN202411612210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing catalytic cracking technology, the pore size of the catalyst is small, making it difficult to effectively transfer mass and diffuse macromolecular crude oil, resulting in a decrease in the yield of low-carbon olefins, and the acidic catalyst promotes hydrogen transfer reaction, resulting in olefin saturation, affecting the yield of olefins.
A composite catalyst of a metal-supported acidic catalyst and an alkaline catalyst is prepared using an equal volume impregnation method. After uniform mixing by ball milling, tableting or spray granulation is performed to form an acid-base composite catalyst, which is combined with the large pores of the alkaline catalyst and the shape selection of the acidic molecular sieve catalyst. pores to achieve collaborative catalysis.
The excellent catalytic cracking performance of crude oil has been achieved, ethylene and acrylic have increased significantly, and the entire synthetic process is green and environmentally friendly, without wastewater discharge.
Smart Images

Figure CN119327505A_ABST
Abstract
Description
1. Technical Field
[0001] The invention relates to the technical field of crude oil processing, and more particularly to a method for preparing an acid-base composite crude oil catalytic cracking catalyst. 2. Background Technology
[0002] Low-carbon olefins such as ethylene, propylene, butene and butadiene are very important basic organic chemical raw materials, which are widely used in the fields of high molecular weight polymers, rubber, surfactants, medicines, dyes, etc. In particular, the production capacity of ethylene and propylene is often regarded as a symbol of the level of petrochemical development in a country or region. At present, about 95% of the world's ethylene and 66% of propylene are produced through the steam thermal cracking process of light raw materials such as naphtha or light diesel. However, with the increasing depletion of conventional crude oil resources, the world's crude oil supply has shown a trend of heavy and inferior development, resulting in a gradual shortage of light cracking raw materials. At this stage, the inherent shortcomings of steam cracking technology, such as the difficulty of processing heavy oil raw materials, the difficulty in regulating the selectivity ratio of propylene and ethylene, and the excessive energy consumption, seriously affect the economic benefits of enterprises and are difficult to adapt to the changes in the future olefin market demand structure.
[0003] In recent years, many technologies for direct catalytic cracking of crude oil to produce more low-carbon olefins have been developed, such as the DCC / CPP process developed by Sinopec Research Institute of Petrochemicals, the PetroFCC process developed by UOP, the HS-FCC process developed by Saudi Aramco, the Indmax process developed by Indian Oil Corporation, the Maxofin process jointly developed by Exxonmobil and Kellog, and the two-stage riser catalytic cracking (TMP) process proposed by China University of Petroleum (East China), which have attracted wide attention from the industry and have been demonstrated in industry. Compared with steam cracking, catalytic cracking technology has the advantages of wide adaptability to raw materials, low reaction temperature, and low energy consumption. However, the catalysts used in the above processes are mainly ZSM-5 and Y-type molecular sieves with small pore sizes, which severely restrict the mass transfer and diffusion of crude oil molecules with larger kinetic diameters, making it difficult for them to enter the molecular sieve channels and accumulate on the catalyst surface in large quantities. On the one hand, this weakens the shape-selective catalytic function of the molecular sieve catalyst, resulting in a decrease in the yield of low-carbon olefins. On the other hand, the crude oil molecules adsorbed on the catalyst surface are prone to deep cracking under the action of acidic sites, resulting in severe coking, which blocks the molecular sieve channels and reduces the carbon utilization rate of crude oil. In addition, ZSM-5 and Y-type molecular sieve acidic catalysts will promote the hydrogen transfer reaction, causing some olefin products to be further saturated into alkanes, which is not conducive to increasing the olefin yield.
[0004] In addition to acidic catalysts, scholars have also conducted extensive research on metal salt-type alkaline catalysts such as calcium aluminate in recent years. The pore structure of this type of catalyst is mainly mesopores and macropores, which is conducive to the diffusion of crude oil macromolecules and adsorption on active sites for cracking reactions; in addition, since solid alkaline catalysts only have dehydrogenation activity but lack hydrogen transfer function, the selectivity of olefins in the product is relatively high. However, due to its lack of acidity or weak acidity, the required cracking temperature is usually high, and its industrial application is relatively small.
[0005] Studies have shown that by combining two or more catalysts with different physical and chemical properties together through a special synthesis method, a composite catalyst material is prepared. Because of its different pore structures and acid-base properties, it exhibits better catalytic reaction performance than a single catalyst in heterogeneous catalytic reactions. Therefore, we try to synthesize an acid-base composite catalyst that combines the large pores and high dehydrogenation activity of the alkaline catalyst with the shape-selective pores and strong acidity of the acidic molecular sieve catalyst, promoting the efficient conversion of crude oil while increasing the yield of low-carbon olefins.
[0006] At present, the preparation schemes of composite catalysts mainly include hydrothermal crystallization and mechanical mixing. Among them, patents CN118183785A, CN105293519A, CN117983289A, CN101767034A and CN115814848A all disclose a two-step crystallization method for preparing composite molecular sieve catalysts, but the above methods consume a lot of water during the synthesis process, and the wastewater pollution problem is serious, and the prepared composite molecular sieve catalyst is essentially still a single acid catalyst, and the influence of hydrogen transfer reaction is not considered. Patents CN117244589A, CN115770614A, and CN114832855A all use a simple mechanical mixing method to compound multiple catalysts, but this method cannot guarantee the full contact and uniform mixing of multiple substrates, and it is difficult to form a ladder channel structure to facilitate the series reaction of crude oil macromolecules. III. Summary of the invention
[0007] To solve the above problems, the present invention provides a method for preparing an acid-base composite crude oil catalytic cracking catalyst, which can provide a pore structure and acid-base properties for synergistic catalysis, has excellent crude oil catalytic cracking performance, and has a high yield of ethylene and propylene. The entire synthesis process is green and environmentally friendly, avoiding wastewater pollution problems.
[0008] The present invention specifically adopts the following technical solutions:
[0009] A method for preparing an acid-base composite crude oil catalytic cracking catalyst comprises the following steps:
[0010] Firstly, a metal-supported acidic catalyst is prepared by an equal volume impregnation method, and 325-500 mesh ultrafine acidic catalyst powder is obtained by sieving; similarly, 325-500 mesh ultrafine alkaline catalyst powder is obtained by sieving; the above two catalysts are mixed evenly by ball milling, and then tableted or spray granulated to obtain an acid-base composite catalyst.
[0011] Furthermore, the active metal component is one or more of Ni, Fe, Ca, Mg, K, Na, Mn, Zn, Cu, and Co.
[0012] Furthermore, the acidic carrier is 3A, 4A, SAPO-34, ZSM-5, or USY.
[0013] Furthermore, the equal volume impregnation process is to mix the prepared metal salt solution with the acidic carrier, stir evenly, stand overnight to dry, and calcine at 550° C. for 4 to 8 hours to obtain the metal-supported acidic catalyst.
[0014] Furthermore, the active metal component loading is 0.01 to 10 wt %.
[0015] Furthermore, the mesh size of the ultrafine acidic catalyst powder is 325-500 meshes.
[0016] Furthermore, the alkaline catalyst is one or more of calcium aluminate, magnesium aluminate, zinc aluminate, magnesium silicate and calcium silicate, and the mesh number of the ultrafine alkaline catalyst powder obtained by sieving is 325-500 meshes.
[0017] Furthermore, the ultrafine acid-base catalyst powders are mixed in a mass ratio of 0.1:1 to 10:1.
[0018] Furthermore, the ball mill has a rotation speed of 200 to 400 rpm / min, and the ball milling time is 1 to 2 hours.
[0019] Furthermore, the tableting pressure is 18-20 MPa, the tableting time is 5-7 min, and the average particle size of the solid particles obtained after spray granulation is 25-200 μm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The method for preparing the acid-base composite crude oil catalytic cracking catalyst provided by the present invention does not consume water, and the entire process is green and environmentally friendly with no wastewater discharge.
[0022] (2) Compared with the traditional mechanical mixing method, the preparation method of the acid-base composite crude oil catalytic cracking catalyst provided by the present invention adds a mixed matrix pretreatment screening step, and uses ultrafine powder as raw material for ball milling mixing to ensure sufficient contact and effective coupling of the acid-base catalyst.
[0023] (3) The present invention provides a method for preparing an acid-base composite crude oil catalytic cracking catalyst, which successfully combines the large pores and high dehydrogenation activity of the alkaline catalyst with the shape-selective pores and strong acidity of the acidic molecular sieve catalyst, and exhibits excellent performance in the crude oil catalytic cracking reaction, and significantly increases the yields of ethylene and propylene. IV. Description of the drawings
[0024] Figure 1 The present invention is a schematic flow diagram of a method for preparing an acid-base composite crude oil catalytic cracking catalyst. V. Specific implementation methods
[0025] The present invention is described in detail below in conjunction with the accompanying drawings and specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0026] Example 1
[0027] 0.02 g of nickel nitrate hexahydrate was weighed and dissolved in 52 ml of deionized water. The solution was stirred on a magnetic stirrer at a speed of 500 rpm / min for 1 h to obtain the required nickel nitrate impregnation solution. The solution was then added dropwise into 50 g of ZSM-5 by an equal volume impregnation method. After stirring evenly, the solution was allowed to stand at room temperature overnight to reach adsorption equilibrium. The solution was dried in an oven at 120° C. for 4 h. After being fully ground, the solution was transferred to a muffle furnace at 550° C. and calcined at a constant temperature for 5 h to obtain a Ni / ZSM-5 catalyst. Ultrafine Ni / ZSM-5 powder with a mesh size of 325 to 500 was obtained by sieving. Ultrafine calcium aluminate powder with a mesh size of 325 to 500 was obtained by sieving. 5 g of ultrafine Ni / ZSM-5 powder and 45 g of ultrafine calcium aluminate powder were placed in a ball mill and fully ball-milled at a speed of 300 rpm / min for 2 h. Finally, the mixture powder was pressed into tablets, crushed, and sieved to obtain acid-base composite catalyst particles.
[0028] Example 2
[0029] 0.02 g of nickel nitrate hexahydrate was weighed and dissolved in 32 ml of deionized water. The solution was stirred on a magnetic stirrer at a speed of 500 rpm / min for 1 h to obtain the required nickel nitrate impregnation solution, and then the solution was added dropwise into 50 g of 4A by an equal volume impregnation method. After stirring evenly, the solution was allowed to stand at room temperature overnight to reach adsorption equilibrium. The solution was dried in an oven at 120° C. for 4 h, and after being fully ground, the solution was transferred to a muffle furnace at 550° C. and calcined at a constant temperature for 5 h to obtain a Ni / 4A catalyst. Ultrafine Ni / 4A powder of 325 to 500 meshes was obtained by sieving. Ultrafine calcium aluminate powder of 325 to 500 meshes was obtained by sieving. 5 g of ultrafine Ni / 4A powder and 45 g of ultrafine calcium aluminate powder were placed in a ball mill and fully ball-milled at a speed of 300 rpm / min for 2 h. Finally, the mixture powder was pressed into tablets, crushed, and sieved to obtain acid-base composite catalyst particles.
[0030] Example 3
[0031] 0.02 g of nickel nitrate hexahydrate was weighed and dissolved in 32 ml of deionized water. The solution was stirred on a magnetic stirrer at a speed of 500 rpm / min for 1 h to obtain the required nickel nitrate impregnation solution, and then the solution was added dropwise into 50 g of 4A by an equal volume impregnation method. After stirring evenly, the solution was allowed to stand at room temperature overnight to reach adsorption equilibrium. The solution was dried in an oven at 120° C. for 4 h, and after being fully ground, the solution was transferred to a muffle furnace at 550° C. and calcined at a constant temperature for 5 h to obtain a Ni / 4A catalyst. Ultrafine Ni / 4A powder of 325 to 500 meshes was obtained by sieving. Ultrafine calcium aluminate powder of 325 to 500 meshes was obtained by sieving. 15 g of ultrafine Ni / 4A powder and 35 g of ultrafine calcium aluminate powder were placed in a ball mill and fully ball-milled at a speed of 300 rpm / min for 2 h. Finally, the mixture powder was spray-granulated to obtain acid-base composite catalyst particles.
[0032] It should be noted that when the claims of the present invention involve numerical ranges, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. In order to avoid redundancy, the present invention describes a preferred embodiment.
[0033] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0034] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
[0035] Example 1
[0036] The performance of the acid-base composite catalyst provided by the present invention was tested through the following application examples, and the evaluation results are shown in Table 1.
[0037] Using light wax oil as raw material, the catalyst samples obtained in Examples 1 to 3 were evaluated for catalytic cracking reaction in a laboratory fixed bed device. The catalyst loading amount was 7.5 g.
[0038] Before the reaction starts, atmospheric pressure nitrogen is introduced into the reaction tube from the top of the reaction tube at a flow rate of 40 mL / min, and the heating furnace is raised to the reaction temperature at a heating rate of 10 ° C / min (subject to the actual measurement of the thermocouple). After reaching the set reaction temperature, the raw materials are pumped into the reaction tube, and the reaction products are led out from the bottom of the reaction tube through a stainless steel tube and then separated into gas and liquid through a low-temperature ethylene glycol solution cold trap. The liquid phase product is collected by a condenser, and the gas phase product is recorded and collected through a drainage device. During the experiment, the reaction time, the quality of the crude oil, the volume of the gas product and the quality of the liquid product should be recorded, and the gas and liquid phase products should be collected for component analysis, and finally the corresponding cracking product yield and distribution should be calculated.
[0039] The gaseous products obtained by the reaction include hydrogen, alkanes below C5, olefins and a small amount of hydrocarbons larger than C5. The gaseous products are quantitatively analyzed using a SCION 456-GC refinery gas analysis gas chromatograph. The liquid products are analyzed by a simulated distillation analyzer (CP-3800GC), and the liquid product cuts mainly include gasoline fraction (IBP~200℃), diesel fraction (200~350℃) and vacuum residue fraction (350~500℃). The quality of the cracked gas is calculated from the volume measured by the drainage device and its gas composition, and the quality of the cracked oil is measured by weighing the liquid product.
[0040] The yield calculation formula of each type of product is as follows:
[0041]
[0042] Table 1 Evaluation results of catalysts
[0043] sample Example 1 Example 2 Example 3 hydrogen 0.41 0.33 0.33 Methane 7.02 10.97 10.67 Ethane 7.14 8 7.89 Propane 3.33 0.84 0.82 Butane 1.38 0.14 0.13 Pentane 0 0 0 C6+ 1.08 0.92 1.04 Ethylene 20.58 26.29 25.68 Propylene 23.33 17.36 17 Butene 8.22 6.71 6.56 Pentene 0.25 0.79 0.7 gasoline 7 7.83 4.50 diesel fuel 0.73 1.83 1.20 VGO 0 0.34 0.17 Gas phase products 72.73 72.35 70.83 Liquid products 8.03 9.99 5.86 Total yield 80.76 82.34 76.69
[0044] As shown in Table 1, in the catalytic cracking application of light wax oil, the total yield of low-carbon olefins in Examples 1 to 3 reached about 50%, among which the ethylene yield of Example 1 reached 20.58% and the propylene yield reached 23.33%; the ethylene yield of Example 2 reached 26.29% and the propylene yield reached 17.36%; the ethylene yield of Example 3 reached 25.68% and the propylene yield reached 17%. The above results show that the acid-base composite crude oil catalytic cracking catalyst provided by the present invention has excellent performance and significantly increases the yield of low-carbon olefins such as ethylene and propylene.
Claims
1. A method for preparing an acid-base composite crude oil catalytic cracking catalyst, characterized in that: The following steps are involved: Firstly, a metal-supported acidic catalyst is prepared by an equal volume impregnation method, and 325-500 mesh ultrafine acidic catalyst powder is obtained by sieving; similarly, 325-500 mesh ultrafine alkaline catalyst powder is obtained by sieving; the above two catalysts are mixed evenly by ball milling, and then tableted or spray granulated to obtain an acid-base composite catalyst.
2. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The active metal component is one or more of Ni, Fe, Ca, Mg, K, Na, Mn, Zn, Cu, and Co.
3. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The acidic carrier is 3A, 4A, SAPO-34, ZSM-5, and USY.
4. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The equal volume impregnation process is to mix the prepared metal salt solution with the acidic carrier, stir evenly, let it stand overnight to dry, and calcine at 550° C. for 4 to 8 hours to obtain the metal-supported acidic catalyst.
5. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The loading amount of active metal components in the metal-supported acidic catalyst is 0.01 to 10 wt%.
6. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The mesh number of the ultrafine acid catalyst powder obtained by sieving is 325-500 meshes.
7. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The alkaline catalyst is one or more of calcium aluminate, magnesium aluminate, zinc aluminate, magnesium silicate and calcium silicate. The mesh number of the ultrafine alkaline catalyst powder obtained by sieving is 325-500 meshes.
8. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The ultrafine acid-base catalyst powders are mixed in a mass ratio of 0.1:1 to 10:
1.
9. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The ball mill speed is 200-400 rpm / min, and the ball milling time is 1-2 h.
10. The method for preparing an acid-base composite crude oil catalytic cracking catalyst according to claim 1, characterized in that: The tableting pressure is 18-20 MPa, and the tableting time is 5-7 minutes; the average particle size of the solid particles obtained after spray granulation is 25-200 μm.
Citation Information
Patent Citations
Preparation method of catalysis material containing ZSM-5 / Y type composite molecular sieve
CN101767034A
Synthesis method of ZSM-5 / Y composite molecular sieve without using template
CN105293519A
Modified composite molecular sieve catalyst and preparation method thereof
CN114832855A
Composite molecular sieve catalyst and application thereof
CN115770614A
ZSM-5 / Y composite molecular sieve as well as preparation method and application thereof
CN115814848A